PERANAN K.H ABDUL MUKTI SEBAGAI TOKOH PENDIDIKAN ISLAM DIKECAMATAN SABAK AUH KABUPATEN SIAK (1960-1975) - Yuliana, Mamik; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: K.H Abdul Mukti is one of the leaders of Islamic Education in Sabak Auh Subdistrict, Siak Regency, as well as other Education Leaders. K. Abdul Mukti also has very large services to promote Education, especially Islamic Education in Bandar Sungai Village, Sabak District, Auh. K.H Abdul Mukti's role in education is proven by the many educational institutions he founded such as schools and mosques as a place to study. In addition to establishing a school and K.H Mosque Abdul Mukti also became one of the pioneering figures in the construction of roads, footballs and markets, precisely in Bandar Sungai Village, Sabak District, Auh. K.H Abdul Mukti also has a lot of activities in the field of social welfare such as preaching through lectures on Friday and public sermons, Wirid-Wirid Recitation, and Recitation of Haul. To find out the role of K.H Abdul Mukti as an Islamic Education Leader in Sabak Auh Subdistrict, the method used is Qualitative, a type of research that is not obtained through statistical procedures or other calculation forms. This type of research is a type of field research to explore and examine data relating to the title. Admissions Respondents from this study were family, community and students of K.H Abdul Mukti. Data collection techniques used were interviews and documentation. Based on the results of these studies it can be concluded that K.H Abdul Mukti has a big role in advancing Islamic Education in the District of Sabak Auh, Siak Regency.Keywords: K.H Abdul Mukti, Role, Sabak Auh District, Siak Regency